Solve the following

Question:

Find $(x+1)^{6}+(x-1)^{6}$. Hence, or otherwise evaluate $(\sqrt{2}+1)^{6}+\sqrt{2}-1^{6}$.

Solution:

The expression $(x+1)^{6}+(x-1)^{6}$ can be written as

$(x+1)^{6}+(x-1)^{6}$

$=2\left[{ }^{6} C_{0} x^{6}+{ }^{6} C_{2} x^{4}+{ }^{6} C_{4} x^{2}+{ }^{6} C_{6} x^{0}\right]$

$=2\left[x^{6}+15 x^{4}+15 x^{2}+1\right]$

By taking $x=\sqrt{2}$, we get:

$(\sqrt{2}+1)^{6}+(\sqrt{2}-1)^{6}=2\left[(\sqrt{2})^{6}+15(\sqrt{2})^{4}+15(\sqrt{2})^{2}+1\right]$

$=2[8+15 \times 4+15 \times 2+1]$

$=2 \times(8+60+30+1)$

$=198$

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now